The mummy (2017) [videorecording (DVD)] - Cruise, Tom, 1962-; Crowe, Russell, 1964-; Wallis, Annabelle, 1984- (Universal Pictures Home Entertainment, 2017)
Thought safely entombed deep beneath the desert, an ancient princess whose destiny was unjustly taken from her is awakened in our current day. Her malevolence has grown over millennia and with it come terrors that defy human comprehension.